2000
DOI: 10.1093/jac/46.6.1029
|View full text |Cite
|
Sign up to set email alerts
|

Features and trends in Helicobacter pylori antibiotic resistance in Lisbon area, Portugal (1990-1999)

Abstract: The features of Helicobacter pylori antibiotic resistance in Lisbon from 1990 to 1999 were studied. Overall resistance rates to amoxycillin, tetracycline, metronidazole, clarithromycin and ciprofloxacin were 0, 0, 30.6, 19.0 and 9.6%, respectively. The incidence of resistance to clarithromycin was much higher in isolates from children (44.8%) than adults (14.6%). For metronidazole, the contrary was observed (children: 19.0%, adults: 32.3%). Ciprofloxacin-resistant isolates were all from adult patients. Concern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
1
2

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 6 publications
9
92
1
2
Order By: Relevance
“…The resistance rate of H. pylori to clarithromycin has been divergent in various studies. For instance, the rate of clarithromycin resistance was reported to be up to 20% in Portugal (12), Saudi Arabia (15), South Korea (16), China (17) and Iran (18), while it has been reported to be 58% in Germany (11) and 32% in Italy (19). In a study carried out by Mohammadi et al (18) in Iran, resistance to clarithromycin was reported to be 17%, which is similar to our findings.…”
Section: Resultssupporting
confidence: 90%
“…The resistance rate of H. pylori to clarithromycin has been divergent in various studies. For instance, the rate of clarithromycin resistance was reported to be up to 20% in Portugal (12), Saudi Arabia (15), South Korea (16), China (17) and Iran (18), while it has been reported to be 58% in Germany (11) and 32% in Italy (19). In a study carried out by Mohammadi et al (18) in Iran, resistance to clarithromycin was reported to be 17%, which is similar to our findings.…”
Section: Resultssupporting
confidence: 90%
“…6 and 9 . 6 %, respectively (Cabrita et al, 2000). On the other hand, Heep et al (2000) noted that secondary H. pylori resistance to clarithromycin and metronidazole after eradication failure was frequently observed in 75 and 58 % of the strains, respectively, but resistance to ciprofloxacin was observed in only 9 % of the strains.…”
Section: S Fujimura and Othersmentioning
confidence: 99%
“…Portugal was reported around the 9.6%, 29 whilst in another study performed in Italy, the resistance was 31%. 30 These differences probably reflect the uses of this compound in other clinical setting, which can vary between countries or regions.…”
mentioning
confidence: 89%